Analisis Vitamin C Pada Buah Pepaya, Sirsak, Srikaya Dan Langsat Yang Tumbuh Di Kabupaten Donggala - Cresna, Cresna; Napitupulu, Mery; Ratman, Ratman (Universitas Tadulako, 2014)
Vitamin C is known as ascorbic acid. The function of vitamin C is to help the synthesis of collagen and antioxidants that the body needs. Vitamin C can be obtained from fruits, and each fruit had different levels of vitamin C. This study aims to determine the levels of vitamin C in the fruit papaya, soursop, sugar apple and complexioned fruit. This study uses a volumetric method that uses a solution of iodine (I2) as the titer, and using starch as an indicator, and each piece studied every day for three days with the same treatment. The results obtained levels of vitamin C in papaya fruits in a row are the first day of 46.89 mg, the second day 34.6 mg, third day and 22.88 mg. Vitamin C in the complexioned fruits are the first day 82.28 mg, the second day 61.31 mg, and third day 37.14 mg. Vitamin C in the sweetsop fruit are the first day 49.83 mg, the second day 35.2 mg, and third day 20.46 mg. And the soursop fruit vitamin C content was obtained on the first day 62.42 mg, the second day 33.44 mg, and third day of 23.14 mg. The results demonstrated that levels of Vitamin C in four fruits had decreased each day since the time of storage.